2020
DOI: 10.7717/peerj.9814
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics of serum β2-microglobulin between viral and bacterial lower respiratory tract infections: a retrospective study

Abstract: Background Lower respiratory tract infection (LRTI) is one of the leading cause of death in children under 5 years old around the world between 1980 and 2016. Distinguishing between viral and bacterial infection is challenging when children suffered from LRTI in the absence of pathogen detection. The aim of our study is to analyze the difference of serum β2-microglobulin (β2-MG) between viral LRTI and bacterial LRTI in children. Methods This retrospective study included children with LRTI caused by a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…ROC curve analysis showed that β 2-MG had high sensitivity and specificity in distinguishing viral from bacterial infection. This study was consistent with our previous study, and elevated β 2-MG concentration might help to distinguish viral from bacterial infections in children with lower respiratory tract infection ( Cai et al, 2020 ). The change of β 2-MG level may be helpful in screening viral infection and avoiding antibiotic abuse.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ROC curve analysis showed that β 2-MG had high sensitivity and specificity in distinguishing viral from bacterial infection. This study was consistent with our previous study, and elevated β 2-MG concentration might help to distinguish viral from bacterial infections in children with lower respiratory tract infection ( Cai et al, 2020 ). The change of β 2-MG level may be helpful in screening viral infection and avoiding antibiotic abuse.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the activation of cytotoxic T cells participate in the immune response to viral infection ( Baugh, Tzannou & Leen, 2018 ; David et al, 2019 ; Langellotti et al, 2020 ). A previous study found that β 2-MG was significantly increased in viral lower respiratory tract infection, and it may distinguish viral infection from bacterial infection ( Cai et al, 2020 ). This study analyzed the distribution characteristics of β 2-MG in children with exanthem subitum and acute URTI.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings suggest that elevated serum β2MG levels are associated with hypoxemia. Some studies have found that an increase in serum β2MG levels is also present during infectious diseases as well as during in ammatory responses [25,27]. In this study, 189 (73.5%) patients had a level of serum β2MG > 3.0 mg/L, and the median serum β2MG levels were found to be elevated in patients with bacterial infection-induced ARDS.…”
Section: Discussionmentioning
confidence: 46%
“…Several previous studies have shown that levels of serum β2MG are higher in patients with in ammatory bowel disease or systemic lupus erythematosus than in healthy controls, suggesting that it might also be a useful biomarker for the assessment of these autoimmune diseases [16,24]. Some research has suggested that β2MG is probably a general biomarker that re ects acute or chronic changes during in ammation and infection [25][26][27]. In addition, elevated levels of serum β2MG have been also observed in patients with haemato-oncological pathology and solid tumours despite their preserved renal function [11,28].…”
Section: Discussionmentioning
confidence: 99%